The Influence Of Organizational Culture, Leadership Style of The Head of The Madrasah, and Work Motivation on The Professional Teachers of Private Ibtidaiyah Madrasahs In Batang Kuis District, Deli Serdang Regency - Amiruddin Siahaan; Tien Rafida; Rahmiyatul Mawaddah (STAI Miftahul Ula Nganjuk, 2022)
The purpose of this paper is to find out the influence of organizational culture, leadership style of madrasah heads, and work motivation on the professional teachers of private ibtidaiyah madrasahs in batang kuis district deli serdang district. This research method, namely This research is a quantitative research with an expost facto research design, namely the variables studied are not controlled and manipulated by the researcher, but the facts are revealed based on the measurement of symptoms that have been owned or testing what will happen. The results of this study are 1. Organizational culture has a direct influence on teacher work motivation by 16.9%, and the remaining 83.1% is an influence outside the variables of organizational culture, this indicates that the higher the organizational culture, the higher the teacher's work motivation. 2. The leadership style of the madrasah head has a direct influence on the teacher's work motivation by 18.7% and the remaining 81.3% is an influence outside the variable The leadership style of the madrasah head, this indicates that the better the teacher's perception of the leadership style of the madrasah head, the higher the teacher's work motivation. 3. Organizational culture has a direct influence on the professional quality of teachers by 19.4% and the remaining 80.6% is an influence outside the variables Organizational culture, this indicates that the better the organizational culture, the higher the professional quality of teachers. 4. The leadership style of the head of the Madrasah has a direct influence on the professional quality of the teacher by 19.5% and the remaining 80.5% is an influence outside the variable The leadership style of the head of the Madrasah, this indicates that the better the leadership style of the head of the Madrasah, the higher the professional quality of the teacher. 5. Work motivation has a direct influence on the professional quality of teachers by 22.1% and the remaining 77.9% is an influence outside the variables Of teacher professional quality, this indicates that the higher the teacher's work motivation, the higher the professional quality of the teacher.